Harmony search freeman chain code (HS-FCC) extraction algorithm for handwritten character recognition - Mohamad, Muhammad `Arif (2015)
In handwritten character recognition, interest in feature extraction has been on the increase with the abundance of algorithms derived to increase the accuracy of classification. In this paper, a metaheuristic approach for feature extraction technique based on Harmony Search Algorithm is proposed using Freeman chain code as data representation. Proposed algorithm is to find the shortest route length and minimum computational time for chain code extraction from the handwritten character thinned binary image. The result is shown to be superior compared to other meta-heuristic approaches such as Differential Equation, Particle Swarm Optimization, Genetic Algorithm and Ant Colony Optimization.